Social Formation of The Terms of Business Tourism in Uzbekistan - Gavharoy Isroiljon kizi (Zien Journals, 2022)
This article provides information on the diachronic and synchronous study of business tourism terms in the territory of Uzbekistan and the analysis of the periodicity of the formation of business tourism terms. The terms of business tourism are explained by the results of statistical analysis through social surveys.
Keywords: tourism; national and cultural civilization; assimilated dexterity; lexical system